2014
DOI: 10.1515/ntrev-2012-0050
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled polysaccharide nanostructures for controlled-release applications

Abstract: Self-assembling polysaccharide nanostructures have moved to the forefront of many fields due to their wide range of functional properties and unique advantages, including biocompatability and stimulus responsiveness. In particular, the field of controlled release, which involves influencing the location, concentration, and efficacy of active pharmaceutical ingredients (APIs), diagnostics, nutrients, or other bioactive compounds, has benefited from polysaccharide biomaterials. Nanostructure formation, stimulus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 125 publications
(154 reference statements)
0
35
0
Order By: Relevance
“…It is well known that acidic polysaccharides are prone to forming spheroidal architectures in aqueous solution by means of calcium-mediated gelation. A typical instance is the Ca 2þ -alginate nanoparticles formed via self-assembly in aqueous environments [42][43][44][45]. In light of this, given that divalent cations, i.e.…”
Section: Nanoparticles Observed In Sundew Adhesivementioning
confidence: 99%
“…It is well known that acidic polysaccharides are prone to forming spheroidal architectures in aqueous solution by means of calcium-mediated gelation. A typical instance is the Ca 2þ -alginate nanoparticles formed via self-assembly in aqueous environments [42][43][44][45]. In light of this, given that divalent cations, i.e.…”
Section: Nanoparticles Observed In Sundew Adhesivementioning
confidence: 99%
“…Signal‐triggered release of substances from chemical systems for various applications , particularly drug release , and more specifically DNA release , for biomedical applications has been extensively studied in the last decades. The controlled DNA release is important for many applications, including gene‐delivery therapy , biosensors , biochips and biocomputing .…”
Section: Introductionmentioning
confidence: 99%
“…The height analysis in the planar image ( Figure 5E,F) revealed the aggregation extent of SAZMP4. A branched, ring-like, helical or an interconnected network structure in the AFM image ( Figure 5A,B) implied molecular self-assembly of SAZMP4, which undergoes a spontaneous process from disorder to order based on the weak, noncovalent interaction of hydrogen bonds and van der Waals forces as well as the hydrophobic effect [41]. These results indicated that SAZMP4 might aggregate at first and then self-assemble to form a long chain; this is why the molecular morphology of SAZMP4 appeared the way it did in SEM and AFM images.…”
Section: Molecular Morphological Propertiesmentioning
confidence: 99%